The Influence of Democratic Parenting Style on Early Childhood Discipline - Aulia, Zahro; Hastuti, Dwi; Surahman, Susilo (JOYCED: Journal of Early Childhood Education, 2026)
Purpose - This study examines the influence of democratic parenting style on early childhood discipline at TK Masyithoh I'anatut Thalibin Pati. Discipline is an essential aspect of character development, fundamentally shaped through appropriate parental guidance. Design/methods/approach – A quantitative approach with a correlational design was employed, involving a purposive sample of 53 parents of children aged 4–6 years. Data were collected using validated and reliable questionnaires covering indicators of open communication, rule enforcement, and self-control. Findings - Simple linear regression analysis revealed that democratic parenting style has a significant positive effect on child discipline. The analysis yielded a coefficient of determination (R2) of 0.944, indicating that 94.4% of the variation in child discipline can be explained by the parenting style. Research implications/limitations - While these findings strongly reinforce the theory that authoritative guidance fosters self-regulation, the exceptionally high R2 value suggests strong internal consistency and potential common method bias within the local context. Originality/value - This study provides empirical support for the effectiveness of democratic parenting style in fostering early childhood discipline and recommends that educators and parents implement communicative and responsive guidance to support optimal character development.